On the road to Mecca: Branding discourses and national identity on coffee shop signage. - Abduljalil Nasr Hazaea; Mutahar Qassem (PLoS ONE)
Commercial branding stands as a discursive and cultural facet of the contemporary global era where competing brands construct their own identities. From a discourse perspective, a brand is discursively constructed on commercial signs. Accordingly, this study examines the interplay between coffee shop branding and national identity in Saudi Arabia. In so doing, the study investigates the competing branding discourses associated with coffee as well as the space given to national identity. To achieve this task, the study developed a conceptual framework grounded on critical discourse analysis (CDA) and linguistic landscape (LL). The data consists of 88 commercial signs of coffee shops collected by driving on a road from Najran to Mecca, Saudi Arabia. The research site was then verified through Google Maps. The data built a communicative event for an empirical mixed-method research design. CDA linguistic and multimodal toolbox was utilized. The analysis showed that three names of coffee are found on the road to Mecca: qahwa (Arabic), coffee (English), and kufi (transliteration). With these names, four discourse are in competition. For globalization, English-Arabic glocal discourse (34%), and English global discourse (8%) are competing to construct coffee branding. For national identity, Arabic local discourse (42%) and Arabic-English glocal discourse (16%) are associated with qahwa; something that gives substantial space (58%) for national identity. These findings enhance our understanding of the linguistic and multimodal dimensions of globalized spaces and their discursive construction of branding at the local scale of globalization. The study recommends further research and suggests some cultural and pedagogical implications for authorities, translation, bilingual awareness, teaching, and learning.